Myelin Development in SIDS: MRI Findings - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The MRI brain scans of 28 SIDS infants were compared with 14 controls at the Neuropathology Unit, University of Sydney, and the Department of Radiology, Royal Prince Alfred Hospital, New South Wales, Australia.